2009
DOI: 10.1056/nejmoa0903812
|View full text |Cite|
|
Sign up to set email alerts
|

Triple-Reassortant Swine Influenza A (H1) in Humans in the United States, 2005–2009

Abstract: From December 2005 until just before the current human epidemic of swine-origin influenza viruses, there was sporadic infection with triple-reassortant swine influenza A (H1) viruses in persons with exposure to pigs in the United States. Although all the patients recovered, severe illness of the lower respiratory tract and unusual influenza signs such as diarrhea were observed in some patients, including those who had been previously healthy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
426
0
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 531 publications
(455 citation statements)
references
References 33 publications
16
426
0
13
Order By: Relevance
“…Shinde et al (2009) reported 11 cases of infection with triple-reassortant swine influenza A (H1) viruses in persons with exposures to pigs in the USA, before the human epidemic caused by influenza viruses of swine-origin.…”
Section: Discussionmentioning
confidence: 99%
“…Shinde et al (2009) reported 11 cases of infection with triple-reassortant swine influenza A (H1) viruses in persons with exposures to pigs in the USA, before the human epidemic caused by influenza viruses of swine-origin.…”
Section: Discussionmentioning
confidence: 99%
“…This divergence has created a substantial antigenic gap between classical swine H1N1 and human seasonal H1N1 viruses. Thus, pigs have become a reservoir of influenza viruses, with the potential to cause an outbreak of major respiratory disease in humans, possibly resulting in a pandemic 13, 20, 21. Genetically, the influenza A virus (pH1N1) is very similar to both the classic swine virus and the North American lineage triple reassortment that has circulated in the United States of subtype H1N1 swine over the past 10 years, occasionally infecting humans during the same period 21, 22…”
Section: Discussionmentioning
confidence: 99%
“…Ces pandémies sont secondaires à la diffusion, dans une population immunologiquement naïve, d'une souche virale modifiée par des cassures antigéniques secondaires à des réassor-timents de segments viraux d'un virus de sous-type A humain avec ceux d'un virus animal le plus souvent d'origine aviaire ou porcine [3][4][5][6]. Le potentiel létal chez l'homme de ce virus recombiné est variable.…”
Section: Vaccins Pandémiques Et Pré-pandémiques Dirigés Contre Le Virunclassified
“…Ces vaccins induisent une bonne réponse immunitaire mais ils sont moins bien tolérés, en raison de la présence d'une enveloppe lipidique à leur surface [28]. 6 www.who.int/csr/disease/influenza/pandemic/en/ [37]. Enfin, l'utilisation d'un autre virus aviaire non pathogène pour l'homme (comme H5N3) pourrait constituer une alternative intéressante par l'induction d'une immunogénicité croisée [38].…”
Section: Vaccins à Virions Entiersunclassified